2008
DOI: 10.1002/eqe.800
|View full text |Cite
|
Sign up to set email alerts
|

Response analysis of rigid structures rocking on viscoelastic foundation

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 29 publications
(31 reference statements)
0
42
0
Order By: Relevance
“…An alternative formulation is however proposed by [8], also on the base of the Housner theory, that can in the present case be further simplified according to the specific expression of I O :…”
Section: Restitution Coefficientmentioning
confidence: 99%
“…An alternative formulation is however proposed by [8], also on the base of the Housner theory, that can in the present case be further simplified according to the specific expression of I O :…”
Section: Restitution Coefficientmentioning
confidence: 99%
“…In equation (13), T is the kinetic energy of the system and Q is the generalized force acting on the system…”
Section: Equation Of Motion Of the Rocking Framementioning
confidence: 99%
“…The substitution of equations (17) and (21) into Lagrange's equation given by (13) results to the equation of motion of the rocking frame for θ(t)<0. …”
Section: Equation Of Motion Of the Rocking Framementioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that both solutions were equivalent, allowing the use of the simple one. The former solution was also studied in [9], whilst the latter was used in [10,11]. ElGawady et al [12] investigated the influence of the material constituting the interface through experimental tests and Vassilou and Makris [13] examined the benefits of different types of isolated base thanks to numerical simulations.…”
Section: Introductionmentioning
confidence: 99%